Auditoría de gestión a la cooperativa de ahorro y crédito “Cristo Rey” de la ciudad de Loja, período 2021. - Ayabaca Imaicela, Arelis Rashel (2023)
The Curricular Integration Work called: "Management audit to the cooperative of savings and credit "Cristo Rey" of the city of Loja, period 2021", was developed as a mechanism of economic, financial and administrative support for the institution examined, for the effect, objectives were set to evaluate the internal control system, determine the level of compliance with legal and regulatory provisions, application of management indicators to measure the efficiency and effectiveness and the preparation of the final audit report. In order to achieve the objectives, several techniques and methods were implemented according to the audit process, starting with the Preliminary Knowledge with the previous visit to the Cooperative, where the necessary information was collected, the “FODA” was established and a general diagnosis was obtained; in the second phase Planning, the internal control system was evaluated and the tools for the next phase were prepared; Execution, where the application of programs and the preparation of working papers that support the report were carried out; in the fourth phase Communication of Results, the preparation and presentation of the final report was carried out; and finally the Follow-up phase, which includes a compliance schedule and implementation of recommendations. In addition, management indicators were applied to evaluate the efficiency and effectiveness of the “COAC-CRISTO REY” According to the results of the internal control evaluation, some shortcomings were found that are not considered serious, but are important to take into account and implement improvements for the process, such as the fact that the institution does not have an internal control manual, there are no activities to promote organizational culture, the projected training has not been met and that certain areas are only trained when they deserve it and according to their needs, since there is no fixed budget for each area but one in general, which causes inequality in staff training; as a result, the respective narrative cards were prepared and the management audit report was presented, with the respective conclusions and recommendations, which will help the institution to meet its objectives and institutional goals in an efficient and effective manner, addressed to the Manager of the "Cristo Rey" Savings and Credit Cooperative of the city of Loja.